In Vitro Studies On Antibacterial Activity Of Physcomitrium Japonicum Hedw. (Funariaceae) - B.L.CHAUDHARY,; SHABANA KHANAM, (International Journal of Pharma and Bio Sciences, 2011)
The antibacterial activity of moss Physcomitrium japonicum (Hedw.) was studied against the various bacteria namely Bacillus subtilis (MTCC-441) , Escherichia coli (MTCC-41) , Staphylococcus aureus (MTCC-740), Pseudomonas aeruginosa (MTCC-424) and Agrobacterium tumefaciens (MTCC-2250) by agar well diffusion technique. The extracts of aqueous and organic solvents were tested against the all bacterial culture. All the extracts showed antibacterial activity against all tested microorganism. The results suggest the potential of P. japonicum for developing a broad spectrum antibacterial formulation in future.